Preference for Averageness in Faces Does Not Generalize to Non-Human Primates - Tomeo, Olivia B.; Ungerleider, Leslie G.; Liu, Ning (Frontiers in Behavioral Neuroscience, 2017)
Facial attractiveness is a long-standing topic of active study in both neuroscience and social science, motivated by its positive social consequences. Over the past few decades, it has been established that averageness is a major factor influencing judgments of facial attractiveness in humans. Non-human primates share similar social behaviors as well as neural mechanisms related to face processing with humans. However, it is unknown whether monkeys, like humans, also find particular faces attractive and, if so, which kind of facial traits they prefer. To address these questions, we investigated the effect of averageness on preferences for faces in monkeys. We tested three adult male rhesus macaques using a visual paired comparison (VPC) task, in which they viewed pairs of faces (both individual faces, or one individual face and one average face); viewing time was used as a measure of preference. We did find that monkeys looked longer at certain individual faces than others. However, unlike humans, monkeys did not prefer the average face over individual faces. In fact, the more the individual face differed from the average face, the longer the monkeys looked at it, indicating that the average face likely plays a role in face recognition rather than in judgments of facial attractiveness: in models of face recognition, the average face operates as the norm against which individual faces are compared and recognized. Taken together, our study suggests that the preference for averageness in faces does not generalize to non-human primates.